Designing a System for Collecting Policy-Relevant Data for the Kurdistan Region-Iraq - Berry, Sandra H. (RAND Corporation, 2014)
Comprehensive and reliable statistics are crucial for policy formulation in any region or country. The Kurdistan Region-Iraq is hampered by the lack of such statistics as it aims to improve infrastructure, encourage private-sector development, attract foreign investment, and create a sustainable economy. This volume examines how the Kurdistan Regional Government can assemble the core elements of a quality data system.